Grade 3–4 cytokine release syndrome is associated with poor survival in haploidentical peripheral blood stem cell transplantation. Issue 8 (3rd July 2021) - Modi, Dipenkumar; Albanyan, Omar; Kim, Seongho; Deol, Abhinav; Ayash, Lois; Ratanatharathorn, Voravit; Uberti, Joseph P.
Abstract: The information on the impact of cytokine release syndrome (CRS) on haploidentical donor peripheral blood stem cell transplant (haploPBSCT) outcomes is limited. We retrospectively evaluated 98 patients who underwent haploPBSCT between June 2012 and June 2019 for the onset and severity of CRS per the ASTCT guidelines. The incidence of CRS was 93% (91/98). Outcomes were compared between grade 1–2 and 3–4 CRS. Eighty-one patients developed grade 1–2 CRS (89%) and 10 (11%) developed grade 3–4 CRS. Compared to grade 1–2 CRS, grade 3–4 CRS experienced adverse survival (73.7% vs. 30%, p <.001), inferior relapse-free survival (64.0% vs. 20%, p <.001), and higher non-relapse mortality (NRM) (16.4% vs. 60%, p <.001) at 1-year. Propensity score-based multivariable analyses revealed worse survival (HR 2.71, p =.04), and higher NRM (SHR 4.51, p =.006) with grade 3–4 CRS. Our study shows that grade 3–4 CRS was adversely associated with survival. Therefore, early identification and preventive strategies are warranted.